Pengembangan Proses Enzimatis Untuk Produksi Biodisel Dari Minyak Jarak Pagar dan Uji Performa Pada Mesin Disel - Dini Cahyandari (TRAKSI, 2008)
oil reserved that belonged to Indonesia is limited. In order that there were some efforts have performed to seek an alternative gr.rn una renewable fuel such as biodiesel. Biodiesel production from Jatropha curcas is basically methanolysis reaction, the reaction of triglyceride with metLanol yield to methyl ester and glycerol. This transesterification is performed enzimatically because it has some advantages: energy save, complete transesterification for high free fatty acid and water easy drawn for glycerol, and no washing.The objectives of this research is ti develop enzymatic process to produce biodiesel from Jatropha curcas by using indigeneous enzyme from papain lateks and husk. The achievements are date for design' scale-upand process condition including kinetics reaction, optimum process and data of engine performance. In first year, designing and fabricating. of enxymatic reactor was done followed by studied of kinetics reaction and process computing. Model building was performed based on Michaelis-Menten theory. Model was postulated and then broken down to empirical equation that will be examined and validated by experimental data gathered. The result in the first year showed that longer in time more biodiesel got in conversion at alter ratio. Lipase activity increased in increasing temperature. The optimum temperature was 51  °C. Adding n-hexane solvent has been able to increase conversion in transesterification reaction and to increase enzymatic reaction rate.